PENERAPAN PRESIDENTIAL THRESHOLD PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 14/PUU-XI/2013 - Liberthin Palullungan; Trifonia Sartin Ribo (Paulus Law Journal, 2021)
Indonesia is a country that implements a presidential system and a multi-party system jointly. The implementation of general elections has been regulated in the 1945 Constitution of the Republic of Indonesia. The presidential threshold is a concept used in proposing candidates for President and Vice President. Proposals are made by political parties or joining political parties by general election participants. This article analyzes the application of the presidential threshold after the Constitutional Court decision Number 114 / PUU-XI / 2013. The purpose of this writing is to determine the application of the Presidensitial threshold after the Constitutional Court decision Number 14 / PUU-XI / 013, and to determine the impact of the Constitutional Court decision number 14 / PUU-XI / 2013 on political parties. The research method used is qualitative and conceptual normative research methods. Based on this article, it is known that the application of the presidential threshold in which political parties must obtain seats 20% of the number of seats in the DPR or 25% of the valid votes nationally in the previous DPR elections, so that making new or small parties will not be able to nominate the President and Vice President themselves, but parties can form a coalition.